Long-term talent development in motorsports - Syarizal, A. R.; Noraili, A. W.; Firdaus, M. Z. M.; Khir, A. Z. M.; Hafzal, A. H. M. (Insights into Economics and Management Vol. 5, 2021)
Spain, Italy, and Japan consider it vital to produce more motorbike racers. The contributions of racers to bike development is substantial. This in turn helps the economy by creating job opportunities for youngsters. Talent identification begins with the identification of potential racers at the pocket bike level to the highest level, which is MotoGP. This paper examines the dualist nature of youth talents as both a student and a racer. The study aims to identify the key aspects that affect their career development in this area. The study employed the qualitative approach and interviewed two racers (13-19 years old) that have participated in Malaysia Super Series and Cub Prix and two racing team owners. The data were collected over a period of three months. The data were analyzed to identify major themes in the nurturing of motorsport talents. The results revealed the key aspects of talent development in motorsports. Qualities and passion are necessary in talent identification and development and in the future career of youth talents as professional racers. Collaborations with education institutions (in terms of knowledge sharing through research activities) may influence their involvement in the long-term development of motorsport talent. Academic support is increasingly needed to ensure effective long-term development of youth racers from the first instance of identification up to the professional level. Additionally, factors like training, diet, time management, and discipline are also important determinants of a youth racer`s performance. Most interviewees agreed that racers faced career challenges as they receive inadequate and improper guidance towards the final phase of the socialization process and specialization to become a professional racer. The opportunities in motorsports are large, and so much attention needs to be focused on them. Certain issues demand actions from the ministry and independent organizations, which will influence policy making and practices inside the track.